Energy spectra of exciton states in disk-shaped GaAs-Ga1−xAlxAs quantum dots under growth-direction magnetic fields (2007)
ABSTRACT: A theoretical study, within the effective-mass approximation, of the effects of applied magnetic fields on excitons in disk-shaped GaAs-Ga1−xAlxAs quantum dots is presented. Magnetic fields are applied in the growth direction of the semiconductor heterostructure. The parity of the excitonic envelope function related to the simultaneous exchange of ze → −ze and zh → −zh is a good quantum number and the wave function, both the odd and even parity, can be expanded as combination of products of the quantum well electron and hole function that preserves the parity with appropriate Gaussian functions. We have simultaneously obtained the energies of the excitonic ground and excited states and discuss the behavior of these energies as a function of the magnetic field.